Atomically dispersed Pt–N4 sites as efficient and selective electrocatalysts for the chlorine evolution reaction - Taejung Lim (Nature Portfolio, 2020)
Chlorine evolution reaction (CER) is a key electrochemical reaction for chemical, pulp, and paper industries, and water treatments. Here, the authors report that an atomically dispersed Pt−N4 site can catalyse CER with high activity and selectivity under a wide range of Cl– concentrations and pH.